RETRACTED ARTICLE: Effects of artificial intelligence aibo intervention on alleviating distress and fear in children - Kyoko Tanaka; Maoko Hayakawa; Chihiro Noda; Akio Nakamura; Chieko Akiyama (BMC, 2022)
Abstract Background Procedures and actions such as injections and immobilization cause distress to children. In the pediatric field, there is a need for interventions and support to alleviate the pain and distress caused by such medical procedures. In recent years, the introduction of robots as a means of distraction has begun to be attempted. Methods In this study, we conducted a non-randomized controlled trial to examine the effect of intervention using 'aibo', a dog-like robot which has artificial intelligence (AI), to promote distraction in children after vaccination. Children between the ages of 3 and 12 years old eligible for the Japanese encephalitis vaccine, and their caregivers were assigned to intervention group or control group. Then, children evaluated their pain and children's behavior were observed by observer. The mean values of Faces pain rating scale scores and observer pain scale scores were compared between groups using an unpaired t-test. Results Fifty-seven children (32 in the intervention group) participated in the study. Results of a t-test with the control group showed that the intervention group using aibo had significantly less pain following the post-vaccination intervention than the control group using stuffed dog (Face Scale, t(55) = 2.582, p = .0125; Behavioral Observation Scale, t(55) = 2.772, p = .00759). The results support the hypothesis that the aibo intervention group will be less distressed and able to calm down more quickly after vaccination than the control group. Conclusion Interactive communicative play intervention by an artificially intelligent aibo before and after painful and frightening medical procedures may alleviate fear and anxiety and prevent medical trauma in children.